Investigation of Risk Factors and Biosecurity Measures Associated with Prevalence of Newcastle Disease Virus in Broiler Farms - Mirza Mienur Meher; Jaisan Islam; Marya Afrin (Turkish Journal of Agriculture: Food Science and Technology)
Newcastle disease (ND) is one of the major viral diseases of poultry, remains a constant threat in poultry farms that causes huge economic losses every year. However, little is known regarding the potential risk factors of the disease in broiler. The study was undertaken to ascertain the potential risk factors and biosecurity measures in ND prevalent broiler farm. A total of 116 broiler farms were considered as a sample size from a different area of Barishal district of Bangladesh in which 19.83% ND prevalence was found. In the findings, the farmers (33.62%) who had training on poultry farming, were significantly less ND positive case (7.69%). Besides this, among the different risk factors and biosecurity measures only shed location, ventilation, vaccination status, feeder and waterer cleaning frequency, visitors accession, pets in the farm, use of disinfectant and seasonal variation had significant effect on ND outbreak. However, among all the factors only farmers training (OR=0.025; 95% CI: 0.001-0.509), shed location (OR=0.035; 95% CI: 0.003-0.390), vaccination against ND (OR=0.017; 95% CI: 0.001-0.435) and use of disinfectant daily (OR=0.011; 95% CI: 0.000-0.294) made a unique statistically significant contribution to the regression model and the predictors had approximately similar strength on reporting ND outbreak. In completion, ND can be reduced in broiler farms by improving the level of common biosecurity, farm management practices, and minimizing the potential risk factors through training of farmers, awareness build-up, and enforcement of these practices on the farms.